Multi-generational culture of c. elegans on a long-term space flight revealed changes in expression of genes involved in longevity, DNA repair,and locomotion - Sue, Mian Then; Nurul-Faizah Jusoh,; Roslan Harun,; Sheila Nathan,; Szewczyk, Nathaniel J.; Stodieck, Louis; Rahman Jamal, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2014)
Scientists are trying to determine the long term effects of exposure to microgravity and space radiation on various cellular and biological functions. We used C. elegans as the model organism to study the changes in gene expression. Wild type worms were grown in a liquid medium using the CHab hardware. The CHab was flown on the STS116 flight to the International Space Station (ISS) and returned to earth on the STS118 flight. Upon landing, surviving worms were extracted and RN Alater added. Ground controls were grown at Bioserve in Colorado and passaged synchronously. RN A was later extracted and mRN A gene expression was analysed using Affymetrix GeneChip® C. elegans Genome Array. The results revealed that 858 known genes were differentially expressed (p-value ≤ 0.05 and fold change ≥ ± 2); namely 608 genes were up-regulated and 250 genes down-regulated. The genes dod-19 and dod-3 which are the downstream effectors of the forkhead transcription factor daf-16 were up-regulated. Daf-16 regulates insulin/TGF signaling pathway that influence metabolic alterations, increased stress and microbial resistance. The glutathione S-transferase (gst-1), Flavin-containing MonoOxygenase (fmo-3) and radiation sensitive genes (rad-51 and him-6) were all up-regulated suggesting responses to oxidative stress. The down-regulation of muscle-related genes (mua-3, col-97, col-109, and col-113) maybe due to reduced mechanical stress in muscle exposed to long-term microgravity. This was the longest exposure of a multi-generational cohort of C. elegans to microgravity which were passaged through at least 10 generations in space. The results suggest key changes in genes involved in ageing, DN A repair, oxidative stress and muscle growth.